Hubungan Forgiveness dengan Resiliensi pada Orangtua yang Memiliki Anak Down Syndrome (LITERATUS, 2023)
The aim of this study was to examine the relationship between Forgiveness and resilience in mothers who have children with Down syndrome. This research is important given the emotional and psychological challenges that mothers often face in this situation. The condition of Down syndrome in children can cause significant psychological stress in the mother, where Forgiveness and resilience are key factors in overcoming these challenges. The research was conducted on 100 mothers who have children with Down syndrome, using a purposive sampling method. Data were collected through questionnaires, using the Forgiveness scale from McCullough and the resilience scale from Reivich and Shatte. The research results show that the empirical average (mean) value for Forgiveness is 73.33 and for resilience is 169.15, indicating that these two variables are in the high category. With a correlation coefficient (r) of 0.459 and a significance level of 0.000 (p<0.01), these results indicate a very significant positive relationship between Forgiveness and resilience. This means that the higher the level of Forgiveness in the mother, the higher the level of resilience. These findings have important implications for the development of support and intervention programs for mothers of children with Down syndrome, emphasizing the importance of emotional and psychological aspects in child care. This research also opens up opportunities for further study regarding other factors that influence maternal emotional well-being in this context.